Social foundations of educational decisions - Fischer, Louis; Thomas, Donald R. (Belmont, California : Wadsworth Publishing Company, 1966)
The purpose of this work is to acquaint students with the social bases of educational processes and institutions. In order to understand the educational process and be able to make intelligent decisions about and within it, one must look systematically at the social forces bearing upon it -some just emerging, some vigorously with us, and some fading into the past.
Part One. Educational decision making -- Part Two. American society and education -- Part Three. Teachers and teaching -- Part Four. Conclusions and cases.
Includes index.
Keywords: EDUCATION